MMP14 from BM-MSCs facilitates progression and Ara-C resistance in acute myeloid leukemia via the JAK/STAT pathway - Jinxian Wu; Xinqi Li; Yin Liu; Guopeng Chen; Ruihang Li; Hongqiang Jiang; Wanyue Yin; Xiqin Tong; Rui Cao; Xianwang Wang; Xiaoyan Liu; Fuling Zhou (Experimental Hematology & Oncology)
Abstract Growing evidence underscores the pivotal impact of crosstalk between leukemic stem cells (LSCs) and mesenchymal stromal cells (MSCs) within their niche on leukemia initiation, progression, and therapy response. Although MMP14 plays an important role in inflammation and cancer, the regulation and role of MSC-derived MMP14 in acute myeloid leukemia (AML) are largely unknown. Here, we found that AML patient-derived MSCs (AML-MSCs) were more supportive of AML cell growth compared to healthy donor-derived MSCs (HD-MSCs). Moreover, AML-MSCs and HD-MSCs showed significant differences in gene expression and protein expression profiles. Knockdown of MMP14 in MSCs inhibited the CFU-F ability of MSC cells and increased the proportion of cells in the G0 phase, thereby inhibiting proliferation. Co-culture with MSCs inhibited the proliferation and cell cycle progression of leukemia cells, while increasing the apoptosis rate, thus impairing the leukemogenic potential of AML cells both in vitro and in vivo. Mechanistic studies revealed that MMP14-mediated alterations in the AML stromal microenvironment are driven by PGE2 secretion and activation of the JAK-STAT pathway, promoting leukemia progression. Notably, inhibition of MMP14 can attenuate the chemotherapy resistance of AML cells induced by MSCs to cytarabine (Ara-C). Together, our study, for the first time, demonstrates the critical role of MSC-derived MMP14 in promoting AML progression and chemoresistance. Targeting MMP14 signaling pathways may offer novel therapeutic options for AML.